LEARNER DIVERSITY IN THE EFL CLASSROOM: ETHNICITY PERSPECTIVES - Harahap, Diah Khoirunnisa; Daulay, Sholihatul Hamidah (Universitas PGRI Sumatera Barat, 2024)
This descriptive qualitative research aimed to investigate learner diversity in the EFL Classroom from an ethnic perspective. In collecting data, the writer used classroom observation and a questionnaire as the instrument. The observation was done to observe students' attitudes or behaviour in the practice EFL classroom, and a questionnaire was done to collect the data on students' ethnicity. The participants of this research were 26 students. In the EFL classroom, learners come from different family backgrounds. They came from different families and ethnicities, such as Javanese, Batak, Minang and Malay. Although the learners came from different family backgrounds, there was no significant difference in their culture because they came from a close living area. The most race/ethnicity is Javanese, with the total number of participants being 18 students. It shows that Javanese students dominated the EFL classroom (69%). The second race/ ethnicity was Batak; the total number of Batak students was 4 (15%), and Minang students were 3 (11.5%). Moreover, only 1 Malay student (3.84%) was in the EFL classroom.